Taxonomic review of the Thysanoptyx Hampson generic complex (Lepidoptera: Erebidae: Arctiinae: Lithosiini). II. The genus Thysanoplisna Volynkin with descriptions of seven new species from Vietnam and mainland China - Volynkin, Anton V. (Zootaxa, 2024)
The Asiatic footman moth genus Thysanoplisna Volynkin, 2023 is reviewed with seven species described as new to science: Th. grandimacula sp. nov., Th. minuta sp. nov., Th. monotona sp. nov., and Th. suffusa sp. nov. from Northern Vietnam, Th. bachma sp. nov. from Central Vietnam, Th. tenebrosa sp. nov. from Southwestern China (Sichuan Province), and Th. hoenei sp. nov. from East China (Zhejiang Province). One taxon is restored to species level from synonymy with Th. signata (Walker, 1854): Th. directa (Leech, 1899), stat. rev. Lectotype is designated for Thysanoptyx directa Leech, 1899. Adults and genitalia of both sexes of all species as well as the type species of the similar genera Caliginoptyx Volynkin & Černý, 2024 and Medioptyx Volynkin & Černý, 2024 are illustrated.